A Primer on Aspects of Cognition for Medical Informatics - Patel, Vimla L. (American Medical Informatics Association, 2001)
As a multidisciplinary field, medical informatics draws on a range of disciplines, such as computer science, information science, and the social and cognitive sciences. The cognitive sciences can provide important insights into the nature of the processes involved in human– computer interaction and help improve the design of medical information systems by providing insight into the roles that knowledge, memory, and strategies play in a variety of cognitive activities. In this paper, the authors survey literature on aspects of medical cognition and provide a set of claims that they consider to be important in medical informatics.